Myoelectric untethered robotic glove enhances hand function and performance on daily living tasks after stroke. (December 2020) - Yurkewich, Aaron; Kozak, Illya J; Ivanovic, Andrei; Rossos, Daniel; Wang, Rosalie H; Hebert, Debbie; Mihailidis, Alex
Introduction: Wearable robots controlled using electromyography could motivate greater use of the affected upper extremity after stroke and enable bimanual activities of daily living to be completed independently. Methods: We have developed a myoelectric untethered robotic glove (My-HERO) that provides five-finger extension and grip assistance. Results: The myoelectric controller detected the grip and release intents of the 9 participants after stroke with 84.7% accuracy. While using My-HERO, all 9 participants performed better on the Fugl-Meyer Assessment-Hand (8.4 point increase, scale out of 14, p < 0.01) and the Chedoke Arm and Hand Activity Inventory (8.2 point increase, scale out of 91, p < 0.01). Established criteria for clinically meaningful important differences were surpassed for both the hand function and daily living task assessments. The majority of participants provided satisfaction and usability questionnaire scores above 70%. Seven participants desired to use My-HERO in the clinic and at home during their therapy and daily routines. Conclusions: People with hand impairment after stroke value that myoelectric untethered robotic gloves enhance their motion and bimanual task performance and motivate them to use their muscles during engaging activities of daily living. They desire to use these gloves daily to enable greater independence and investigate the effects on neuromuscular recovery.